“Screen Time” and Psychopathology in Children and Adolescents - Rafael, Alexandra (2020)
Introduction: Screen availability has been associated with negative effects. We intend to characterize and compare the “screen time” in children and adolescents from the Vila Nova de Gaia area, with and without psychopathology.  Material and Methods: Observational study, with a convenience sample and self‑questionnaires from October 1, 2018 to June 31, 2019 to patients followed in Primary Health Care and Child and Adolescent Psychiatry consultation.  Results: We obtained a sample of 223 participants, 184 with (82.5%) and 39 without (17.5%) psychopathology. The majority presented a “screen time” higher than recommended (71.4%), with a higher level in those with psychopathology (p = 0.006). We found the same regarding the use of devices to fall asleep or background TV (p = 0.024 and 0.008, respectively). Covisualization was more frequent in participants without psychopathology (p = 0.045). “Screen time” higher than recommended, background TV and visualization remained significant after logistic regression (p = 0.029, p = 0.024 and p = 0.013, and OR = 3.741 [CI 1.148‑12.194]; OR = 3.494 [CI 1.175 ‑10.392] and OR = 0.249 [CI 0.083‑0.750] respectively).  Discussion: The results are consistent with what is pointed out in other studies about a possible association between “screen time” and psychopathology. It will be important to assess the causal effect of this association.  Conclusion: “Screen time” is excessive and more frequent in participants with psychopathology. The standardization of recommendations and adaptation to the Portuguese reality are of increasing relevance nowadays.